Critical success factors in implementing teaching factory-based competency for voca-tional high school students - Sintha Wahjusaputri; Bunyamin Bunyamin; Tashia Indah Nastiti (LPMPP Universitas Negeri Yogyakarta, 2021)
The teaching factory concept is the basis for a new model that attempts to integrate academic and industrial worlds. This study aims to identify and explore critical success factors in implementing the teaching factory model. Learning activities that are carried out in work environments are able to provide students with relevant learning experiences and develop teachers’ learning objectives which in turn will improve the overall quality of teaching and learning processes in which knowledge about industrial worlds is constructed. This research used qualitative and quantitative methods, adopting Kitchenham’s approach to identify the critical success factors and using reliability and validity testing to validate the critical success factor items. This research was conducted in five vocational high schools in Central Java Province, with the respondents of 140 students. This research shows that there were 27 critical success factors of teaching factory implementation, three of which are the main factors: business and industrial worlds, schools and teachers, and students.